Sesotho Address Forms - Akindele, Dele Femi (Linguistik Online, 2008)
Address forms constitute an integral part of Basotho sociolinguistic etiquette. They are regarded as a kind of emotional capital that may be invested in putting others at ease. They are indicators of deference, politeness and markers of social distance. (Fasold 1990, Akindele 1990, 1991, 1993) This paper examines the address forms used by the Basotho people. It analyzes and discusses the various types and the factors determining their use. The discussion of address forms in Sesotho focuses on First Name, Title plus First Name, Title plus Last Name, Nickname, Multiple Names, and Teknonym. Drawing data from semi-literate and literate urban and rural population of Maseru district of Lesotho, it was found that the commonest form of address used by the Basotho people is title plus first name. e.g. ntate Thabo (father Thabo), ’m’e Puleng (mother Puleng), ausi Maneo (sister Maneo), abuti Mahao (brother Mahao). It is used by close relations, associates, and familiar people in both formal and informal situations.